Estudio de factibilidad para la comercialización de barras energéticas con ingredientes del Pacífico Colombiano en la ciudad de Cali (2020)
This research work aimed to validate the feasibility of marketing cereal bars with fruits of the Colombian Pacific in the city of Cali, as an alternative of income and productivity for a female head of household and victim of displacement due to the armed conflict of the country. For this, the bibliographic review was made, reflecting the theories and arguments that supported the entire development of the research, in addition, instruments of analysis and collection of information were applied in order to identify the feasibility of the market, technical, legal, administrative and financial. A descriptive qualitative research was used, based on the deductive method, and a survey and interview were applied to two market sectors such as consumers and potential distributors of the product in such a way that it will be possible to identify market acceptance and distribution channels.